Structure and Sorption Characteristics of NiCrxFe2 – xO4 Ferrite Powders - V.S. Bushkova; I.P. Yaremiy; R.P. Lisovskiy; B.V. Karpyk (Журнал нано- та електронної фізики)
Powders of nickel-chromium ferrites were prepared by sol-gel technology with participation of auto-combustion. X-ray analysis showed the presence of only one phase, which corresponded to the cubic structure of spinel space group Fd3m. Cation distribution on tetrahedral and octahedral sites showed that the powder Ni-Cr ferrite belong to the inverse spinels. Distances between ions of elementary lattice of spinel structure were calculated. The average size of coherent scattering regions of powders was found to be in the range of 23 to 43 nm. It was found that the X-ray density dx and anionic parameter u increase, but the lattice parameter a decreases linearly with increasing content of Cr3+ ions. The specific surface area S∑ of investigated powders is in the range 7.2 – 17.1 m2/g. In nickel-chromium ferrite powders present meso- and micrpores, and mesopores with effective diameter of 3.9 nm are dominated.